(untitled) (Bulletin of Innovative Research, 2026)
This article explores a systematic approach to improving coaching activities in line with modern requirements. In particular, it introduces the “Leader–Coach” model, which evaluates the performance of athletes and coaches using a system of indicators corresponding to international standards. The model proposes 10 key test indicators to assess athletes’ physical and technical-tactical readiness, as well as a 10-indicator rating tool for coaches to regularly self-evaluate their work. This system enables coaches to objectively measure their team’s performance, compare results with global standards, and identify weaknesses to focus on. The practical implementation principles of the proposed indicator system are described, and an initial survey of coaches reveals that systematic evaluation methods are not yet widely adopted in coaching practice. The findings underscore that implementing an indicator-based evaluation mechanism in coaching is crucial for enhancing coaches’ qualifications and improving sports performance.